EVALUASI SISTEM AKUNTANSI KEUANGAN DALAM PENGELOLAAN DANA DESA PADA DESA TALANG PERAPAT KECAMATAN SELUMA BARAT KABUPATEN SELUMA - Ahmad Sumarlan; Lulu Saputri ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
The accounting system in the management of village funds always emphasizes on the implementation of the principles of accountability, transparency, participatory and responsive, so that later it will be realized the implementation of good governance at the village government level. humans who do not have professional accountants. The problem raised in this study is whether the financial accounting system in the management of village funds in Talang Perapat Village, West Seluma District, Seluma Regency Has Been Done According to the Village Fund Management System Standards and the purpose of this study is to find out whether the financial accounting system in managing village funds in Talang Perapat Village Seluma Barat Subdistrict Seluma Regency is in accordance with the financial accounting system standards for managing village funds. The results of this study note that overall, the performance of village financial management in Talang Perapat Village, West Seluma District, Seluma District has been carried out in accordance with the standards of village fund management set by the government. Keywords: Financial Accounting System in Village Fund Management